Accelerated curing of glued-in threaded rods by means of inductive heating – Part III: transient curing. Issue 8 (11th June 2021) - Ratsch, N.; Böhm, S.; Voß, M.; Adam, M.; Wirries, J.; Dreves, N.; Vallée, T.
ABSTRACT: Accelerated curing of glued-in rods (GiR) has been demonstrated in recent papers to represent an interesting option to shorten dramatically the process time. It has been shown that once heated up within minutes, GiR require meaningfully longer to cool down; it is posited that the cooling phase significantly contributes to the curing of the adhesive. This hypothesis has been experimentally tested in the study presented herein on GiR consisting of M16-8.8 threaded steel rods bonded into blocks of laminated veneer lumber (LVL) with a cross section of 120 × 120 mm 2 considering four different two-component adhesives (one polyurethane, and three epoxies). Accelerated curing was achieved by transient heating regimes, in which temperatures were raised to different peak temperatures, followed by their cooling. Results indicate that, depending upon the adhesive, transient heating has, for some adhesives, the potential to achieve joint capacities comparable to cold-cured reference GiR, but that is not true for, in particular, 2K polyurethanes. Comparisons between experimental data and results obtained through the characterisation of the curing kinetics pointed out the complex relationship between the development of joint strength and that of chemical conversion degrees.